IDENTIFICATION OF HUMAN BEINGS BY MORPHOLOGICAL CHARACTERIZATION OF THEIR TEETH IN FORENSIC CASES (Journal of Forensic Medicine & Toxicology, 2013)
Teeth are the most durable parts in the body as they are resistant to environmental assaults such as incineration, decomposition, trauma, mutilation. They are the most resistant parts to destructions of most kinds to survive temperatures over 16000C and remain virtually intact long after other soft or skeletal tissues have decayed. Though teeth are resistant to environmental assaults but they are mostly effected by diseases which result in decay. However, apart from their general characters, teeth possess highly individualistic characteristics, which varies from person to person. In view of the fact that teeth are least effected by the environmental insults and as a result, maintains its integrity in majority of the cases, as compared to the other body tissues, the present study is aimed at morphological characterization of different types of extracted human teeth samples.
Keywords: Teeth; Morphology; General Characters; Individual Characters; Identification